Aid to Nonpublic Education, 1971-72. Hearings Before the Subcommittee on Education of the Committee on Labor and Public Welfare, United States Senate. Ninety-Second Congress, First and Second Sessions on Aid to Nonpublic Education, December 2, 1971, and January 11, 1972 - Congress of the U.S., Washington, DC. Senate Committee on Labor and Public Welfare; Congress of the U.S., Washington, DC. Senate Committee on Labor and Public Welfare ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1972)
This report contains statements by Stephen Kurzman, various Catholic parochial school representatives, Hebrew school representatives, Protestant representatives, ACLU personnel, and others advocating or opposing aid to nonpublic schools. Much of the material deals with permissible types of aid to parochial schools in light of recent United States Supreme Court decisions. Also included are relevant articles and publications on aid to nonpublic schools. (Photographs and pages 25-27, 41, 153-155, 187-188, 337-357, and 522-524 may reproduce poorly.) (JF)
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Court Litigation; Educational Finance; Educational Vouchers; Federal Aid; Federal Legislation; Federal Programs; Parochial Schools; Private School Aid; Shared Services; State Aid; State Church Separation